Determining Purchase Decisions: Analysis of Electronic Word Of Mouth and Digital Marketing (Marketing Management Literature Review) - Ridho Rafqi Ilhamalimy; Hapzi Ali; M. Ridho Mahaputra (Siber Nusantara of Economic and Finance Review, 2024)
The purpose of writing this Literature Review Paper is to determine the influence of Electronic Word Of Mouth and digital marketing variables on purchasing decisions. Using qualitative methods and Library Research. The research results show that green marketing influences purchasing decisions, digital marketing influences purchasing decisions, Electronic Word Of Mouth and digital marketing together influence purchasing decisions.